2015
DOI: 10.1007/s10585-015-9732-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular targets and pathways involved in liver metastasis of colorectal cancer

Abstract: We here summarize the current view of molecular mechanisms involved in the dissemination process of colorectal cancer cells to the liver as deduced from preclinical models. We focus on molecular aspects of the current understanding of the biology of liver metastases formation and survival, both being crucial for identification and validation of possible therapeutic targets and review the latest findings elucidating some features of the liver as a metastatic niche. In more detail, we outline the role of proteas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 126 publications
3
36
0
Order By: Relevance
“…Although we cannot establish a direct causal link between those previous functional studies and our present results, the gene expression patterns obtained point to circulating blood leucocytes as one plausible source of the pro-angiogenic and pro-tumourigenic systemic environment. Our present results also provide some candidates for mediating the stimulation of cancer cell invasiveness, such as S100P, HGF, MMP9 and ADAM9 [29], which were found to be upregulated in the group of patients with infection. Moreover, our previous investigations suggested that the inflammatory reaction in response to infection leads to an increased expression of local and circulating pro-angiogenic factors, particularly vascular endothelial growth factor (VEGF), which might also facilitate the growth of residual tumour cells [14].…”
Section: Discussionsupporting
confidence: 61%
“…Although we cannot establish a direct causal link between those previous functional studies and our present results, the gene expression patterns obtained point to circulating blood leucocytes as one plausible source of the pro-angiogenic and pro-tumourigenic systemic environment. Our present results also provide some candidates for mediating the stimulation of cancer cell invasiveness, such as S100P, HGF, MMP9 and ADAM9 [29], which were found to be upregulated in the group of patients with infection. Moreover, our previous investigations suggested that the inflammatory reaction in response to infection leads to an increased expression of local and circulating pro-angiogenic factors, particularly vascular endothelial growth factor (VEGF), which might also facilitate the growth of residual tumour cells [14].…”
Section: Discussionsupporting
confidence: 61%
“…Low TIMP1 and PAI1 expression in CD44v6 kd cells deserves further elaboration. Low PAI1 [81] and TIMP1 [82] expression can contribute to loss of invasion. However, TIMP1 may also promote metastases by preserving MET expression and PI3K/Akt activation and promoting HIF1α and miR-210 upregulation, which both require cooperation with the tetraspanin CD63 [83].…”
Section: Discussionmentioning
confidence: 99%
“…Our study demonstrated that during metastasis, there is an interaction of different pathways that involve different genes. A previous study established that CRC progression to liver colonization involves extracellular matrix organization [72,73], and another study established that IGF regulation is also involved [74,75]. We showed that the interaction of extracellular matrix organization, regulation of IGFs and IGBPs, signal transduction and the immune system pathways result in CRC metastasis to the liver.…”
Section: Discussionmentioning
confidence: 60%